2022
DOI: 10.3390/toxics10040190
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of Endocrine Disruptors and the Pesticide Roundup® Induce Oxidative Stress in Rabbit Liver When Administered under the Long-Term Low-Dose Regimen: Reinforcing the Notion of Real-Life Risk Simulation

Abstract: Humans are exposed to xenobiotic mixtures daily through the long-term, low-dose regimen. Investigations designed to simulate this exposure profile approach the real-life risk simulation (RLRS) idea of modern toxicology. The purpose of the present study was to investigate the effects of 12-month exposure of New Zealand rabbits to a xenobiotic mixture comprising seven endocrine disruptors (EDs), which are chemical substances raising great concerns for human health, as well as the herbicide glyphosate, and its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Gut health may also have an influence on brain function via the gut-brain axis [ 42 ]. Overall, there is a need for new studies exploring the links between glyphosate and human health effect markers at environmentally relevant concentrations alone or in combination with other pollutants, searching for links with observed effects found in animal and in vitro studies (e.g., Vardakas et al, 2022) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gut health may also have an influence on brain function via the gut-brain axis [ 42 ]. Overall, there is a need for new studies exploring the links between glyphosate and human health effect markers at environmentally relevant concentrations alone or in combination with other pollutants, searching for links with observed effects found in animal and in vitro studies (e.g., Vardakas et al, 2022) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aside from the NHL issue but due to its systemic detection in the human body, glyphosate may theoretically enter various organs including the liver. In consideration of these aspects, a variety of reports fo-cused on a possible hepatotoxic potential of glyphosate in both, humans [268] and animals [269,270]. High LTs have been observed in a farmer from India with acute liver failure following glyphosate poisoning, who acutely ingested 25 mL glyphosate and had a history of chronic low dosed exposure to glyphosate and alcohol use: serum activities of ALT were 1311 U/L and AST 1021 U/L [271].…”
Section: Glyphosate and Cordycepinmentioning
confidence: 99%
“…Mechanistic views of steps leading to liver injury by glyphosate are primarily based on animal studies [263,269,280]. Consensus exists that glyphosate produces ROS in the hepatocytes, which in turn cause injurious changes of cell protein and structural membrane proteins via unsaturated lipid peroxidation under regulation of antioxidants, GSH, and catalase [269,280].…”
Section: Glyphosate and Cordycepinmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations using laboratory animals designed to evaluate the toxicological profile of pesticide mixtures, administered at concentrations below the existing regulatory limits, have revealed the manifestation of detrimental effects when assessed by metabolomics contrary to the conventional biochemical measurements ( 89 ). Furthermore, previous studies have reported that exposure to low levels of pesticides under the long-term, low-dose regimen perturbs the redox homeostasis and induces oxidative stress, thus causing adverse effects on the organism level in the long term ( 90 , 91 ). In the present study, organic raw honey samples were used, which are free of pesticides ( 92 ).…”
Section: Discussionmentioning
confidence: 99%